2015
DOI: 10.1007/s10909-015-1307-9
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Dependence Observed in Quadrupolar Collective Excitation of a Trapped BEC

Abstract: We report the experimental observation of the collective excitations induced in a magnetically trapped 87 Rb Bose-Einstein condensate. Low-lying mode excitations were studied by tracking the condensate's center-of-mass displacement, and its aspect ratio as a function of the hold time in the trap. We were able to partially control the modes onset by modulating the amplitude of the additional field gradient used to excite the BEC. The measured excitation frequencies were found to be in good agreement with the li… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 25 publications
2
10
0
1
Order By: Relevance
“…33). They found that this oscillation has the same frequency as it was found for the quadrupolar mode [209]. Furthermore, the behavior of the amplitude and the frequency of this oscillation, when the excitation amplitude A exc is increased, is the same as the one obtained for the quadrupolar mode [209].…”
Section: Momentum Distribution Of a Turbulent Trapped Becsupporting
confidence: 64%
See 1 more Smart Citation
“…33). They found that this oscillation has the same frequency as it was found for the quadrupolar mode [209]. Furthermore, the behavior of the amplitude and the frequency of this oscillation, when the excitation amplitude A exc is increased, is the same as the one obtained for the quadrupolar mode [209].…”
Section: Momentum Distribution Of a Turbulent Trapped Becsupporting
confidence: 64%
“…In contrast to the previous data, where the hold time t hold was fixed, in Ref. [209] the momentum distribution was studied during different hold times, as seen in Fig. 33.…”
Section: Momentum Distribution Of a Turbulent Trapped Becmentioning
confidence: 97%
“…In previous works, the transverse momentum distribution of excited Bose gases was used to reconstruct the 3D momentum distribution ( ) using the inverse Abel transform (47) and to study the coupling with collective modes. (49)(50) Here, the same idea is applied, but our procedure allow us to explore not only the azimuthally averaged cloud, but also its angular sections, allowing us to analyze the anisotropy of˜ ( ).…”
Section: Methods To Extract the Momentum Distributionmentioning
confidence: 99%
“…In this thesis, we study three ways to quantify the non-equilibrium regimes produced by the action of a oscillatory excitation in Bose gases, with the same excitation protocol that was used in previous works. (39,(46)(47)(48)(49)(50) We focus on studies of momentum distribution, powerspectrum of fluctuations, and continuous entropy to probe non-equilibrium regimes in cigarshaped trapped gases in the searching of turbulence. The apparatus for performing these experiments prepares an ultracold quantum gas of some nano-Kelvins in a magnetic trap and applies a well controlled oscillatory magnetic excitation.…”
Section: Structure Of This Thesismentioning
confidence: 99%
“…During this project, we have worked in understanding the effects of this perturbations, mainly in the transition from a non perturbed state to an state were evidences of turbulence is found. The main studies were published in references (33,(43)(44) and other are submitted or in preparation. Also, in search for new methods to produce turbulence, we have successfully implemented the technique of topological phase imprinting (45)(46) to produce multicharged vortices.…”
Section: This Thesismentioning
confidence: 99%